Improving Parents’ Knowledge through Ultra Processed Food Education in RA Fatanah, Padang - Dewi, Risti Kurnia; Martfida, Rahmi; Satriya, Muhammad Agung (Warta Pengabdian Andalas, 2025)
Ultra-Processed Foods (UPFs) are industrially manufactured products high in sugar, salt, and fat, with minimal whole-food content. The increasing consumption poses significant health risks, particularly for children. This community service program aimed to improve parents’ knowledge and awareness regarding the importance of limiting UPF intake and promoting balanced nutrition consumption. The program was conducted at RA Fatanah, Padang City, from June to July 2025 and involved 22 parents selected through total sampling. Nutrition education was delivered via a lecture method supported by PowerPoint materials, leaflets, and booklets. Participants completed pre- and post-tests to assess changes in knowledge. The proportion of individuals with low knowledge decreased from 18.2% to 0%, while those with high knowledge increased by 22.8%. On average, participants’ scores rose by 18 points after the intervention. Overall, this program demonstrated that structured nutrition education effectively enhances parental knowledge. Strengthening educational initiatives may contribute to reducing UPF consumption and supporting improved dietary behaviors within families.